Low frequency laser for major recurrent aphthous stomatitis. Clinical case - Perez-Flores, Antonieta (2023)
Recurrent aphthous stomatitis (minor, major or herpetic) is one of the most frequent bucodental diseases, of multifactorial etiology and with genetic predisposition. The diagnosis of this pathology is clinical, and based on the clinical history it can be discriminated with other ulcerative pathologies. Low power laser therapy (LLLT) is proposed as a non-invasive treatment, acting as a cellular photo modulator, which reduces pain, inflammation, and stimulating tissue regeneration, preventing damage. This article reports an 11-year-old boy with a 4-month-old painful wound on the posterior edge of the tongue that appeared after a bite, in which clinical examination revealed a yellowish lesion with reddened areas, surrounded by a whitish halo with rounded edges. LLLT was used for the treatment, after one week the pain decreased, the patient started to eat properly, after 15 days a reduction of the reddish edges of the lesion was observed, after one month the lesion had almost completely remitted. LLLT is described as an effective, non-invasive treatment, which reduces symptoms and improves the patient’s quality of life promoting the healing of the lesions.